PROFIL SELF CONTROL MAHASISWA BIMBINGAN DAN KONSELING DALAM MENGATASI PROKRASTINASI AKADEMIK DI STKIP PGRI SUMATERA BARAT - Yogga Bristone; Zulfikar Zulfikar; Septya Suarja (Universitas Borneo Tarakan, 2021)
ABSTRACTThe problem of this research is motivated by the existence of students who are less able to control themselves in the lecture process, there are students who like to procrastinate in completing lecture assignments, and students who like to be late in attending lecture classes. The purpose of this study is to describe: student self-control in overcoming academic procrastination in terms of the ability to control behavior, the ability to control the stimulus, the ability to anticipate an event or events, the ability to interpret events or events, and the ability to make decisions. quantitative descriptive The research population was 280 students. The sampling technique used is simple random sampling. The number of samples in this study was 164 respondents. The instrument used is a questionnaire. Data analysis with interval scores. The results of this study revealed that in general students' self-control in overcoming academic procrastination was in the high category. Furthermore, it can be seen from the indicators: 1) ) Self control of students in overcoming academic procrastination based on indicators of ability to control behavior is in the high category, 2) Self control of students in overcoming academic procrastination based on indicators of ability to control stimulus is in the fairly high category, 3) Self control of students in overcoming academic procrastination based on indicators of the ability to anticipate an event or event is in the high category, 4) Self-control of students in overcoming academic procrastination based on indicators of ability to interpret events or events is in the high category, 5) Self-control of students in overcoming academic procrastination based on indicators of ability decision making is in the fairly high category. Based on the findings of this study, it is recommended for students to be able to further improve self-control so that they are able to overcome academic procrastination in lectures. Keywords : Self Control, Academic Procrastination ABSTRAKPermasalahan penelitian ini dilatarbelakangi dengan masih adanya mahasiswa yang kurang dapat mengontrol dirinya dalam menjalani proses perkuliahan, adanya mahasiswa yang suka menunda dalam menyelesaikan tugas perkuliahan , dan mahasiswa yang suka terlambat dalam mengikuti kelas perkuliahan. Tujuan dari penelitian ini adalah untuk mendeskripsikan: self control mahasiswa dalam mengatasi prokrastinasi akademik dilihat dari aspek kemampuan mengontrol perilaku, kemampuan mengontrol stimulus, kemampuan mengantisipasi suatu peristiwa atu kejadian, kemampuan menafsikan peristiwa atau kejadian, dan kemampuan mengambil keputusan.Penelitian ini dilakukan dengan menggunakan metode deskriptif kuantitatif Populasi penelitian adalah 280 mahasiswa. Teknik pengambilan sampel dengan menggunakan simple random sampling. Jumlah sampel dalam penelitian ini 164 orang responden. Instrumen yang digunakan berupa angket. Analisis data dengan skor interval. Hasil penelitian ini mengungkapkan secara umum self control mahasiswa dalam mengatasi prokrastinasi akademik berada pada kategori tinggi. Selanjutnya dilihat dari indikator: 1) ) Self control mahasiswa dalam mengatasi prokrastinasi akademik berdasarkan indikator kemampuan mengontrol perilaku berada pada kategori tinggi, 2) Self control mahasiswa dalam mengatasi prokrastinasi akademik berdasarkan indikator kemampuan mengontrol stimulus berada pada kategori cukup tinggi, 3) Self control mahasiswa dalam mengatasi prokrastinasi akademik berdasarkan indikator kemampuan mengantisipasi suatu peristiwa atau kejadian berada pada kategori tinggi, 4) Self control mahasiswa dalam mengatasi prokrastinasi akademik berdasarkan indikator kemampuan menafsirkan peristiwa atau kejadian berada pada kategori tinggi, 5) Self control mahasiswa dalam mengatasi prokrastinasi akademik berdasarkan indikator kemampuan mengambil keputusan berada pada kategori cukup tinggi. Berdasarkan temuan penelitian ini direkomendasikan kepada mahasiswa agar dapat lebih meningkatkan self control sehingga mampu untuk mengatasi prokrastinasi akademik dalam perkuliahan. Kata Kunci : Self Control, Prokrastinasi Akademik